2018
DOI: 10.1038/s41598-018-19674-7
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Functional Criticality of Human Brain during Alzheimer’s Disease Progression

Abstract: The progression of Alzheimer’s Disease (AD) has been proposed to comprise three stages, subjective cognitive decline (SCD), mild cognitive impairment (MCI), and AD. Was brain dynamics across the three stages smooth? Was there a critical transition? How could we characterize and study functional criticality of human brain? Based on dynamical characteristics of critical transition from nonlinear dynamics, we proposed a vertex-wise Index of Functional Criticality (vIFC) of fMRI time series in this study. Using 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 42 publications
(43 reference statements)
0
31
0
Order By: Relevance
“…Montreal Cognitive Assessment is an efficient and rapid screening tool for cognitive dysfunction involving memory, executive function, and attention (Jiang et al, 2018) and has moderate specificity and high sensitivity (Mclennan et al, 2011). Previous studies have found that MoCA scores significantly correlate with both structural and functional brain alterations in SCD Shu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Montreal Cognitive Assessment is an efficient and rapid screening tool for cognitive dysfunction involving memory, executive function, and attention (Jiang et al, 2018) and has moderate specificity and high sensitivity (Mclennan et al, 2011). Previous studies have found that MoCA scores significantly correlate with both structural and functional brain alterations in SCD Shu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, many groups have also observed lower connectivity between these regions in individuals with SCD [18,[76][77][78][79]. Others have reported no difference from control [60], or intricate patterns of greater and lower functional connectivity in individuals with SCD [51][52][53][54][55], suggesting that a complex reorganization of processing responsibilities across network nodes may occur. Multifaceted patterns of increased and decreased connectivity between regions could reflect breakdown in processing within a subnetwork that shifts processing load to more intact components of the broader network.…”
Section: Brain Network Functional Connectivity In Subjective Cognitivmentioning
confidence: 99%
“…vIFC has successfully detected abnormalities in human brain dynamics during AD progression [5]. However, it remains unclear whether vIFC in healthy brains is associated with neurodevelopment, physiological or behavioral measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The vIFC method has been described in detail in our previous publication [5]. Considering the three properties designed in vIFC, increased temporal variations, increased within-group correlations, and decreased between-group correlations, the formula is as follows: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation